The landslides mechanism on the slopes of mount rinjani due to the july 2018 Lombok earthquake - Muhammad Zuhdi; Syamsuddin Syamsuddin; Bakti Sukrisna (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The Lombok earthquake that occurred in succession, which began at the end of July 2018, triggered landslides on several slopes on Mount Rinjani. The vibrations caused by the earthquake make the slopes unstable due to a decrease in the normal force as a component of the frictional force that binds the deposited material on the mountain slopes. The standard power is one factor that influences the friction force as a material binding to resist landslides. Under ordinary conditions, the average pressure depends on mass, gravity, and the slope's slope. During an earthquake, the normal force can be significantly reduced, causing landslides to occur. The slope stability angle shows the maximum slope angle susceptible to landslides due to an earthquake shock. The greater the peak ground acceleration (PGA) due to an earthquake, will have a landslide effect at a smaller tilt angle. The means that a significant shock due to an earthquake on a slope will be able to launch a landslide on a gentle slope, whereas a small shock can only slide a steep slope with a large angle. From the calculation of slope stability, which depends on the static friction coefficient, and PGA, which depends on the earthquake magnitude and the distance of the earthquake source from the slopes of Mount Rinjani, it gives a maximum value of 61.9o and a minimum value of 45.76o.